Strengthening International Presence: Networking Strategies for Indonesian SMEs - Diana, Nur; , Sudarmiatin (International Journal of Business, Economics, and Social Development, 2024)
The low export performance of SMEs in Indonesia is a significant problem in supporting national economic growth because SMEs are often less able to take advantage of international market opportunities compared to large companies. One of the critical determinants of SME exports is networking and partnership relationships. This study uses a quantitative descriptive approach to analyze the role of networking and partnerships in supporting SME exporters entering the international market. The study was conducted through a survey of 67 SME exporters in East Java who are members of the Indonesian Chamber of Commerce, using a questionnaire as a data collection instrument. The results of the study indicate that SME exporters face various obstacles in marketing, human resources, finance, access to information, and the business environment. However, networking and partnerships have been proven to support their export activities. Strategic partners who play a role include government agencies, business partners, business associations, chambers of commerce, state-owned and private companies, universities, and support from family. This support includes information on international market data, business opportunities, potential analysis, access to capital, promotion, and competitive strategies in the global market. These findings indicate that SMEs that build good networks and partnerships can overcome various obstacles and challenges and gain significant benefits from entering the international market.